Father presence, adolescent girls’ resilience, psychological security, and achievement goal orientation: examining direct and indirect associations - Zhou, Jiayi; Wei, Xueyan; Xue, Lingfang (Frontiers in Psychology, 2024)
In the developmental research, studies on the importance of fathers in the parent-child relationship is insufficient, especially the father-daughter relationship. Thus far, a few studies have investigated whether father presence influences adolescent daughters’ resilience. Therefore, this study investigated the extent to which intermediary factors affect the relationship between father presence and daughters’ resilience. A total of 718 Chinese female high school students participated in a questionnaire survey. The results showed father presence was positively related to resilience in female high school students. Additionally, psychological security fully mediated the relationship between father presence and daughters’ resilience, whereas achievement goal orientation partially mediated this relationship; specifically, the mastery-approach and performance-approach orientations. The results highlight the importance of considering the meaning and implications of father presence and daughter’s resilience in Chinese culture.